Ships and their timber source as indicators of connections between regions (AmS-Skrifter, 2020)
The precise dating and determination of the source of timbers in shipwrecks found around the coasts of the North Sea and the Baltic Sea, through dendrochronology allows us to see connections between north and  south, east and west throughout the region and to a high chronological precision. In this paper we take a look at results of recent analyses of timber from ships, and timber and barrel cargoes, to try to draw a chronological picture, from the twelfth to seventeenth centuries, of links between regions, through transport in oak ships and trade of timber. Archaeological finds of oak from timber cargos in shipwrecks and fine art objects (painted panels and sculpture) show the extent to which timber was shipped from Hanseatic towns along the southern Baltic coast, to western and north-western Europe.